Posaconazole for the treatment of allergic bronchopulmonary aspergillosis in patients with cystic fibrosis. (25th February 2019) - Periselneris, J; Nwankwo, L; Schelenz, S; Shah, A; Armstrong-James, D
Abstract: Objectives: Allergic bronchopulmonary aspergillosis (ABPA) can accelerate lung function decline in patients with cystic fibrosis (CF). Antifungal medication can be used in addition to systemic corticosteroid treatment. Patients and methods: We evaluated Aspergillus -specific IgE and the use of therapeutic drug monitoring of triazoles in a retrospective analysis of 32 patients. Results: There was a significant reduction in Aspergillus IgE with posaconazole but not with other triazoles ( P = 0.026). Aspergillus IgE levels were inversely correlated with the therapeutic drug level of posaconazole. Conclusions: These data suggest that posaconazole is better than comparator azoles at decreasing serological response to Aspergillus and that this response was better with therapeutic levels of posaconazole.